Community Medicine and Neuroscience Explaining the Biological Mechanisms of Art Interventions - Labib, Mohammad (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2025)
Background: Community medicine increasingly integrates interdisciplinary approaches to address complex determinants of health, including biological, psychological, and social factors. Art-based interventions (ABIs, such as music therapy, visual arts, narrative medicine, and performance) have shown promise in promoting community health, yet their underlying biological mechanisms remain underexplored. Objective: This study aims to examine the contribution of neuroscience in elucidating the mechanisms through which ABIs exert health benefits, thereby reinforcing their scientific legitimacy within the field of community medicine. Methods: A total of 10 peer-reviewed articles were selected based on relevance, methodological quality, and alignment with inclusion criteria. Thematic synthesis and content analysis were used to extract and categorize data on neurological, psychological, and immunological effects of ABIs. Results: The review identified consistent activation of key brain regions, such as the prefrontal cortex, amygdala, anterior cingulate cortex, and insula, during artistic engagement. These neural activities were linked to improvements in emotional regulation, cognitive flexibility, and empathy. Conclusion: Neuroscience provides a biologically grounded explanation for the efficacy of ABIs, validating their integration into community medicine. By influencing neural, endocrine, and immune pathways, ABIs contribute to psychosocial resilience, health promotion, and disease prevention. These findings support the strategic inclusion of arts in public health frameworks, particularly in underserved or culturally diverse communities.